Sense of evil - Hooper, Kay (New York Bantam Books, 2003)
After a series of murders in which the victims are all blondes who did not resist their attacker, police chief Rafe Sullivan calls in the FBI for assistance and is concerned by the atypical methods of the responding agent, Isabel Adams.
112858
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Police -- Southern States -- Fiction; Government investigators -- Fiction; Serial murders -- Fiction; Psychics -- Fiction; Fiction -- Mystery & Detective -- Police Procedural; Fiction -- Occult & Supernatural; Fiction -- Supernatural -- Thrillers; Fiction -- Thrillers -- Suspense; Government investigators; Police; Blondes -- Fiction; Psychological fiction; Mystery fiction; Southern States -- Fiction; Psychological fiction; Romance fiction; Suspense fiction; Thrillers (Fiction); Detective and mystery fiction; Fiction